2022
DOI: 10.3389/fgene.2022.936658
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a survival nomogram for gastric cancer based on the cancer genome atlas of m6A-related genes

Abstract: Objective: Based on TCGA database, a prediction model for 1-, 3-, and 5-year overall survival rates of gastric cancer (GC) patients was constructed by analyzing the critical risk factors affecting the prognosis of gastric cancer patients.Method: Clinicopathological features as well as gene signature of GC patients were obtained from TCGA database. Patients were randomly divided into a training cohort and an internal validation cohort. Independent predictors of GC prognosis were analyzed by univariate and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…The management of STAD is a critical clinical issue due to the rapid disease progression and dismal prognosis. A lack of potent tumor-killing initiators and selective tumor-targeting therapeutic medications limits the efficiency of precision medicine for STAD ( 24 ). A recent study discovered that alterations to the mechanism of programmed tumor cell death may enhance STAD’s targeted therapeutic benefits ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The management of STAD is a critical clinical issue due to the rapid disease progression and dismal prognosis. A lack of potent tumor-killing initiators and selective tumor-targeting therapeutic medications limits the efficiency of precision medicine for STAD ( 24 ). A recent study discovered that alterations to the mechanism of programmed tumor cell death may enhance STAD’s targeted therapeutic benefits ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical management of STAD is a serious clinical concern due to rapid disease progression and poor prognosis. The level of precision medicine for STAD is hampered by a lack of effective tumor-killing initiators and selective tumor-targeting therapeutic medicines ( 23 ). A recent study found that alterations of the mechanism of programmed tumor cell death may potentiate the targeted therapeutic impact of STAD ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, aberrant RBM15-driven m 6 A deposition may stabilize certain oncogenic transcripts by connecting them to IGF2BP1-3 m 6 A readers that promote transcript stability and are overexpressed in different cancer types (Li et al 2019;Cai et al 2021;Wang et al 2021). The connection between m 6 A, RBM15/B, and cancer has received increased attention in recent years; however, further research is necessary to clarify the exact roles that RBM15/B-driven m 6 A deposition plays in tumorigenesis and whether RBM15/B expression levels could be used as biomarkers (Li et al 2019;Wang et al 2022). TCGA data for RBM15 and RBM15B show different mutations dispersed over the entire genes (Fig.…”
Section: Rbm15 and Rbm15b In Cancermentioning
confidence: 99%